Plant Growth-Promoting Bacteria (PGPB) integrated phytotechnology: A sustainable approach for remediation of marginal lands - Poria, Vikram; Dębiec-Andrzejewska, Klaudia; Fiodor, Angelika; Lyzohub, Marharyta; Ajijah, Nur; Singh, Surender; Pranaw, Kumar (Frontiers in Plant Science, 2022)
Land that has little to no utility for agriculture or industry is considered marginal land. This kind of terrain is frequently found on the edge of deserts or other arid regions. The amount of land that can be used for agriculture continues to be constrained by increasing desertification, which is being caused by climate change and the deterioration of agriculturally marginal areas. Plants and associated microorganisms are used to remediate and enhance the soil quality of marginal land. They represent a low-cost and usually long-term solution for restoring soil fertility. Among various phytoremediation processes (viz., phytodegradation, phytoextraction, phytostabilization, phytovolatilization, phytofiltration, phytostimulation, and phytodesalination), the employment of a specific mechanism is determined by the state of the soil, the presence and concentration of contaminants, and the plant species involved. This review focuses on the key economically important plants used for phytoremediation, as well as the challenges to plant growth and phytoremediation capability with emphasis on the advantages and limits of plant growth in marginal land soil. Plant growth-promoting bacteria (PGPB) boost plant development and promote soil bioremediation by secreting a variety of metabolites and hormones, through nitrogen fixation, and by increasing other nutrients' bioavailability through mineral solubilization. This review also emphasizes the role of PGPB under different abiotic stresses, including heavy-metal-contaminated land, high salinity environments, and organic contaminants. In our opinion, the improved soil fertility of marginal lands using PGPB with economically significant plants (e.g., Miscanthus) in dual precession technology will result in the reclamation of general agriculture as well as the restoration of native vegetation.